(untitled) (Indian Journal of Public Health Research & Development, 2020)
A functional simulation approach has been tempted between clinically proven lapin and human septic arthritis, in which twenty experimentally induced lapin S aureus septic arthritis and 20 natural human S.aureus septic arthritis were the human simulation materials. Lapin synovial fluids were aspirated by the veterinarian of the team and human synovial fluids were aspirated by the rheumatologist of the team. Direct synovial fluid Giemsa stained smears were showing neutrophilic infiltration responses both for lapin and human. Cell free synovial supernatants for lapin and human were found positive for S.aureus agglutinins up to the titre of 32 .Sandwich eliza for TNF alpha,INF gamma and IL4 for lapin synovial fluid and same for human synovial fluid TNF alpha, INF gamma and IL4. Lapin knee joint synovial mucosal compartment was found valid model for human synovial mucosal compartment during the course of S, aureus septic arthritis. Likewise, the lapins knee joints synovial mucosal cytokine responses simulate that of man .Herd immunity concept was found operable in both lapin and human populations. Herd tripartite nature of the immune responses as low moderate and high responders both for rabbit and man.The herd immune plots were of skewd type for TNF alpha, normal distribution curves to INF gamma and IL4 both for lapin and human. This functional simulation study appear to be novel contribution in knee joint synovial mucosal cytokine responses.